2015
DOI: 10.1007/s10439-015-1384-6
|View full text |Cite
|
Sign up to set email alerts
|

Bone Pose Estimation in the Presence of Soft Tissue Artifact Using Triangular Cosserat Point Elements

Abstract: Accurate estimation of the position and orientation (pose) of a bone from a cluster of skin markers is limited mostly by the relative motion between the bone and the markers, which is known as the Soft Tissue Artifact (STA). This work presents a method, based on continuum mechanics, to describe the kinematics of a cluster affected by STA. The cluster is characterized by Triangular Cosserat Point Elements (TCPEs) defined by all combinations of three markers.The effects of the STA on the TCPEs are quantified usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…It was shown that, if the most accurate TCPEs could be identified at each time step, the orientation and position errors would be reasonably small, especially during stance. This result confirms that there is no synchronous rigid motion of the entire cluster relative to the underlying bone Solav et al, 2016), and that instantaneous optimal selection of sub-clusters has the potential to greatly reduce pose estimation errors. The TCPEs which obtained the smallest pose estimation errors varied greatly across time and between orientation and position, and were composed of almost all markers.…”
Section: Discussionsupporting
confidence: 69%
“…It was shown that, if the most accurate TCPEs could be identified at each time step, the orientation and position errors would be reasonably small, especially during stance. This result confirms that there is no synchronous rigid motion of the entire cluster relative to the underlying bone Solav et al, 2016), and that instantaneous optimal selection of sub-clusters has the potential to greatly reduce pose estimation errors. The TCPEs which obtained the smallest pose estimation errors varied greatly across time and between orientation and position, and were composed of almost all markers.…”
Section: Discussionsupporting
confidence: 69%
“…Consequently, the results are dependent on the selected registration algorithm [22], [23], since there is no closed-form solution for this registration. Using our method, this problem is avoided entirely, since the correspondence between surface points is inherently tracked using 3D-DIC, thereby allowing a closed-form solution to be applied [24]. For the same reason, only 3D-DIC allows for local full-field deformation and strains measurement, while other scanning techniques can only evaluate out-of-plane displacements.…”
Section: Introductionmentioning
confidence: 99%
“…First, only one motor task (treadmill walking) was studied. Second, a marker-cluster made of all markers was analysed while combinations of multiple marker-clusters selected with different rationales (Barré et al, 2015;Grimpampi et al, 2013;Solav et al, 2016) have not been investigated. Third, the analysis was based on a modal description of the STA and the corresponding energy (i.e.…”
Section: Discussionmentioning
confidence: 99%